Silver nanoparticle induced immunogenic cell death can improve immunotherapy - Ara Sargsian; Xanthippi Koutsoumpou; Hermon Girmatsion; Can Egil; Kiana Buttiens; Carla Rios Luci; Stefaan J. Soenen; Bella B. Manshian (Journal of Nanobiotechnology)
Abstract Cancer immunotherapy is often hindered by an immunosuppressive tumor microenvironment (TME). Various strategies are being evaluated to shift the TME from an immunologically ‘cold’ to ‘hot’ tumor and hereby improve current immune checkpoint blockades (ICB). One particular hot topic is the use of combination therapies. Here, we set out to screen a variety of metallic nanoparticles and explored their in vitro toxicity against a series of tumor and non-tumor cell lines. For silver nanoparticles, we also explored the effects of core size and surface chemistry on cytotoxicity. Ag-citrate-5 nm nanoparticles were found to induce high cytotoxicity in Renca cells through excessive generation of reactive oxygen species (ROS) and significantly increased cytokine production. The induced toxicity resulted in a shift of the immunogenic cell death (ICD) marker calreticulin to the cell surface in vitro and in vivo. Subcutaneous Renca tumors were treated with anti-PD1 or in combination with Ag-citrate-5 nm. The combination group resulted in significant reduction in tumor size, increased necrosis, and immune cell infiltration at the tumor site. Inhibition of cytotoxic CD8 + T cells confirmed the involvement of these cells in the observed therapeutic effects. Our results suggest that Ag-citrate-5 nm is able to promote immune cell influx and increase tumor responsiveness to ICB therapies.